The changing significance of ethnic and class resources in inmigrant businesses : The case of korean inmigrant businesses in Chicago - Yoon, In-Jin
tbls., gráfs., map.
pp. 303-332
Keywords: Chicago; Estados Unidos de America; Inmigrantes; Comerciantes; Coreanos; Clases Sociales; Movilidad Social